2005
DOI: 10.1002/pssa.200521186
|View full text |Cite
|
Sign up to set email alerts
|

The stress field of a dislocation array in an ultra thin anisotropic heterogeneous bicrystal

Abstract: The problem of a dislocation parallel and close to two free surfaces of a thin foil made up of two plates of different nature, using anisotropic elasticity, is treated numerically. Different applications are presented for the thin homogeneous crystals Al/Al and Cu/Cu and also for the thin bicrystal Al/Cu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[12][13][14] Even for the simpler twodimensional ͑2D͒ problem of periodic misfit dislocations, only the elastic field for layered structures containing a few layers has been calculated. 9,10 Based on published reports, we concluded that the elasticity associated with a multilayered crystal system containing a biperiodic array of interfacial misfit dislocations is still far from complete.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…[12][13][14] Even for the simpler twodimensional ͑2D͒ problem of periodic misfit dislocations, only the elastic field for layered structures containing a few layers has been calculated. 9,10 Based on published reports, we concluded that the elasticity associated with a multilayered crystal system containing a biperiodic array of interfacial misfit dislocations is still far from complete.…”
Section: Introductionmentioning
confidence: 89%
“…The elastic fields for a multilayered composite containing one periodic ͑or biperiodic͒ array of interfacial misfit dislocations have been investigated by using Fourier or double Fourier series expansion methods. [9][10][11][12][13][14] However, this method is limited and time consuming as it requires the inversion of a 6N ϫ 6N matrix for a laminated medium containing N interfaces. This is especially problematic when N is very large ͑say, N = 100, 1000, or 10 000͒, not to mention that the inversion of the 6N ϫ 6N matrix is only for one term in the Fourier or double Fourier series.…”
Section: Introductionmentioning
confidence: 99%